Strategi Penjangkauan dan Pemuridan kepada Kaum Marjinal di Kawasan Kumuh daerah Barata Jaya – Rumah Pompa Bratang, Surabaya - Sinaga, Reynold Aristokrat; Prayogo, Thomas Handoyo; Prayogo, Kezia Refina; Simanjuntak, Ferry (Abdi Jurnal Publikasi, 2023)
Abstract: This Community Service research describes outreach and discipleship strategies to reach marginalized people in slum areas in the southern area of Surabaya, which in this case was pioneered by the GBI House of Grace Surabaya church. Marginal People in this research description highlights groups of people who are classified as disadvantaged and below the poverty line. This research examines outreach and discipleship efforts to develop the faith of marginalized people in the slum areas of Surabaya. Through a qualitative approach, we analyze community strategies and church approaches in providing access to health services, education, and especially the growth of faith in God. The findings highlight the challenges and opportunities in improving the welfare of marginalized people and provide insight for the body of Christ or spiritual community to have the same burden and calling in outreach to marginalized people in Surabaya and other cities in Indonesia or various countries to have an inclusive approach in improving living standards and faith of marginalized communities